Prevalence and pathology of Cephalopina titillator infestation in Camelus bactrianus from Xinjiang, China - Huaibing Yao; Mengli Liu; Wanpeng Ma; Haitao Yue; Zhanqiang Su; Ruiqi Song; Qiang Ma; Ling Li; Zhuangyuan Wu; Yingjun Ma; Gangliang Chen; Baojiang Chen; et al. (BMC Veterinary Research, 2022)
Abstract Background In camels, nasopharyngeal myiasis is caused by the larvae of Cephalopina titillator, which parasitize the tissues of nasal and paranasal sinuses, pharynx, and larynx. C. titillator infestation adversely affects the health of camels and decreases milk and meat production and even death. However, the C. titillator infestation in Bactrian camels has not been widely studied. Methods The present study was conducted to determine the prevalence and risk factors of C. titillator in Bactrian camels of northwestern Xinjiang. Suspected larvae recovered from infested camels were evaluated for C. titillator by microscopy and polymerase chain reaction. Nucleotide sequences of the partial mitochondrial cytochrome c oxidase subunit I (COX1) and cytochrome b (CYTB) genes from the C. titillator of camels were aligned from the NCBI database. Furthermore, the gross and histopathological alterations associated with C. titillator infestation were evaluated via pathological examination. Results Of 1263 camels examined 685 (54.2%) camels were infested with suspected C. titillator larvae. Different larval stages were topically detected in the nasal passages and pharynx of the camel heads. Microscopy analysis of the pharyngeal mucosa tissue revealed necrotic tissue debris and some inflammatory cells. Molecular detection of the larval COX1 and CYTB genes indicated that pathogen collected in Bactrian camels was C. titillator. The epidemiological study demonstrated that the prevalence rate of C.titillator infestation was significantly higher in camels of Bestierek Town Pasture (67.2%) and Karamagai Town Pasture (63.6%) compared to Kitagel Town Pasture (38.7%) and Qibal Town Pasture (35.8%) (P < 0.05). No significant difference was observed between the prevalence rates in male (52.6%) and female (54.6%) camels (P > 0.05). The prevalence was higher in warm (64.2%) than that in cold (48.4%) seasons (P < 0.001). The prevalence in camels with non-nomadic method (67.2%) was significantly higher than in animals with nomadic method (47.5%) (P < 0.001). The prevalence of C.titillator infestation was significantly higher in animals of aged 5–10 (60.1%) and aged > 10 (61.1%) years old compared to those of aged < 5 (31.7%) years old camels (P < 0.001). Conclusion Our results confirm that there is a high prevalence of C. titillator in Bactrian camels from Xinjiang, closely related to age, season, pasture environment, and husbandry methods. Developing prevention, diagnosis, and control programs to prevent transmission is necessary.